Study of the Preparation of Bone Scaffold Via the Replication Technique - Razzaq, Mohaimen Ali (American Journal of Botany and Bioengineering, 2025)
Bone scaffolds play a vital role in orthopedic and dental applications by facilitating bone regeneration through biomimetic structural support. Despite extensive research, optimizing scaffold porosity, mechanical strength, and biocompatibility remains a challenge. This study investigates the preparation of bone scaffolds using replication techniques with polymer, ceramic, and metal-based templates, focusing on material selection, template design, and sintering or curing protocols. The process involves coating sacrificial templates with tailored slurries followed by thermal treatment to produce highly porous, interconnected structures. The results demonstrate that scaffold properties such as pore size (60–350 μm), porosity (up to 90%), and compressive strength can be effectively controlled, ensuring compatibility with physiological loads and cellular environments. These findings highlight the replication method's potential to produce cost-effective, customizable scaffolds suitable for clinical use in tissue engineering and orthopedic repair.